Strategic Analysis (BAZNAS) SUMUT on Impossible Assistance and Development in Productive Zakat Management - Asmuni Asmuni; Andri Soemitra; Ermi Suhartyni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research is motivated by the problem of Mustahik’s success rate in managing productive zakat at the National Amil Zakat Board (BAZNAS) North Sumatradid not show the results as expected. This research aims: 1) To know the Mustahik Mentoring and Mentoring Program in management productive zakat on the National Amil Zakat Board (BAZNAS) North Sumatra. 2) To analyze the strategy of the National Zakat Agency (BAZNAS) North Sumatra on Assistance and Guidance of Mustahik inmanagement productive zakat. 3) To analyze the strategy of the National Zakat Agency (BAZNAS) North Sumatra on Assistance and Guidance of Mustahik inmanagement productive zakat in accordance with the concept of sharia. The research method used is qualitative research methods, data collection through observation, interviews and documentation and questionnaires. The data analysis used is interactive analysis (Miles and Huberman) to analyze the potential of the National Zakat Agency. (BAZNAS) North Sumatra, Mentoring and Guidance program and Mustahik's perception. SWOT analysis as the basis for formulating the strategy of the National Zakat Agency (BAZNAS) North Sumatra in the productive Mustahik Assistance and Development program. The results show that Mustahik in managing productive zakat has not received assistance and guidance from the National Zakat Agency (Amil Zakat).BAZNAS) North Sumatra.